The Incidence and Risk Factors of Lens-iris Diaphragm Retropulsion Syndrome during Phacoemulsification - Lim, Dong Hui; Shin, Dong Hoon; Han, Gyule; Chung, Eui-Sang; Chung, Tae-Young (Korean journal of ophthalmology, 2017)
In the present study, the incidence and risk factors of lens-iris diaphragm retropulsion syndrome (LIDRS) were evaluated. Patients who underwent cataract surgery using phacoemulsification between June 2014 and December 2014 were included in the study. The preoperative ocular biometric and intraoperative surgical parameters were examined. The incidence of LIDRS and various risk factors were analyzed using an independent t-test, Pearson's chi-square test, and univariable and multivariable logistic regression analyses. Among 124 eyes of 124 patients, 100 (80.6%) had no LIDRS and 24 (19.4%) had LIDRS. LIDRS occurred in 13 of 31 vitrectomized eyes (41.9%) and 11 of 93 non-vitrectomized eyes (11.8%). Based on univariable analysis, age (odds ratio [OR], 0.920; p = 0.001), vitrectomized eye (OR, 5.038; p = 0.001), spherical equivalent (OR, 0.778; p < 0.001), axial length (OR, 1.716; p < 0.001), anterior chamber depth (OR, 3.328; p = 0.037), and 3.0 mm vs. 2.2 mm incision size (OR, 4.964; p = 0.001) were statistically significant risk factors associated with the development of LIDRS. Conditional multivariable logistic regression showed that vitrectomized eye (OR, 3.865; 95% confidence interval [CI], 1.201 to 12.436; p = 0.023), long axial length (OR, 1.709; 95% CI, 1.264 to 2.310; p = 0.001), and 3.0 vs. 2.2 mm incision size (OR, 3.571; 95% CI, 1.120 to 11.393; p = 0.031) were significant independent risk factors associated with LIDRS. LIDRS is a relatively common occurrence and was found to be associated with vitrectomized eye, long axial length, and larger incision size. Evaluating risk factors prior to cataract surgery can help reduce associated morbidity.